Do the Incentive Changes Affect Employee Performance? - Mukhlis, Akhmad; Safitri, Rini (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This purpose of this study is analyse the effect of incentive changes to the employee performance: effect of the rule changes of the award size for scientific publication authors, Intellectual Property Rights (IPR) and book publishers at one of the universities in Indonesia on the number of submissions for author awards. The research will apply quantitative analysis which will focus on award size changing that applied at one of the universities in Indonesia. The paired sample t test analysis will be used to investigate the changes of the total submission before and after the changes of the award size. It the result of this study finds that there is no significant affect incentive changes and employee performance (total of submissions after increasing award of authors) Therefore, this study shows that the nominal changes are not a significant factor to make lecturers motivated to write. It can be said that the effectiveness of the remuneration system is also influenced by good design and implementation. As an originality, this research is the only research that discusses remuneration in the university environment by focusing on the performance of lecturers in conducting research and scientific work.